Peningkatan Kompetensi Sumber Daya Manusia Dalam Internasionalisasi Pendidikan - Entrisnasari, Fantika Vera; Khuriyah, Khuriyah (Universitas Islam Negeri Raden Intan Lampung, 2023)
In the era of globalization, all are affected by the strong currents, including in the field of education. Facing the current of globalization, the world is also competing to create a system so that it can become a reference for education at the global level, as well as the human resources produced so that they can compete at the global level. Many Indonesian universities also organize internationalization of education, but judging by the world ranking of Indonesian universities, none of them are in the top 100 or even the top 200. So it is necessary to evaluate and analyze the causes of the failure. From various causes, it is hypothesized that there is a lack of human resource competence in the internationalization of education. So it is necessary to determine the criteria for evaluating policies related to HR, for further data on various alternatives that can solve existing problems. The policy alternatives are then analyzed for their achievements against the evaluation criteria so that universities implementing the internationalization of education receive recommendations to improve the policies that have been implemented so far. This research is a type of qualitative research, the stages of analysis used are; (1) verify, define, and detail the problem, (2) establish evaluation criteria, (3) identify alternatives, (4) evaluate alternative policies, (5) present alternatives and differentiate between them. There are ten policy recommendations that can be considered by managers of institutions that will use them.